**Step-by-step explanation:**

(39 + 33) - 94

39 + 33 = 72

94 - 72 =22

**Answer:**

p = 3

q = 4

**Step-by-step explanation:**

p + 2q = 11 --------------------(I)

p = 11 - 2q

2p + q = 10 --------------------(II)

Substitute p = 11 -2q in equation (II)

2(11 - 2q) + q =10

2*11 - 2q *2 + q = 10

22 - 4q + q = 10

22 - 3q = 10

-3q = 10 - 22

-3q = -12

q = -12/-3

**q = 4**

Plugin q = 4 in equation (I)

p + 2q = 11

p + 2*4 = 11

p + 8 = 11

p = 11 - 8

**p = 3**

**Answer:**

She can afford to take 6 people to the movies in total

** Step-by-step explanation:**

50/8 = 6.25

The answer should just be 6 because you can't take 0.25 of a person